PERTUMBUHAN AWAL TITI (Gmelina moluccana) - Febian. F. Tetelay; Lily Pelupessy; Yacob Rahayaan; Bronie S Serlaloy; Hein A. Nimreskossu; Rizaldy R. Tuharea (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2020)
Titi or Gmelina moluccana is a type of the Lamiaceae family that grows in Maluku. Although this species is local, there is still very little information about its growth. This study aims to determine the growth of this species from planting in the field until the sixth year, environmental factors that affect its growth. Data collected in the form of plant height and diameter, air temperature, humidity, soil pH, soil moisture, sunlight intensity. Environmental factors are then related to plant height and diameter to determine environmental factors that affect the growth of these plants through multiple linear regression equations. Besides, the mean annual increment and the current annual increment is also calculated to determine the cycle of this plant. Based on the results of research, Titi plants up to the sixth year have an men annual increment and the current annual increment is 0.99 meters/year and 1.46 meters for height and 1.62 cm/year and 2.50 cm for diameter. Until the sixth year this species has not entered the techniquecycle, while for woodworking purposes, this species can be harvested at the age of 24.5 years. Environmental factors that affect the growth of Titi are soil pH and soil moisture.